New indices for home nursing care resource disparities in rural and urban areas, based on geocoding and geographic distance barriers: a cross-sectional study. Issue 1 (December 2015) - Lin, Shyang-Woei; Yen, Chia-Feng; Chiu, Tzu-Ying; Chi, Wen-Chou; Liou, Tsan-Hon
Abstract Background Aging in place is the crucial object of long-term care policy worldwide. Approximately 15.6–19.4 % of people aged 15 or above live with a disability, and 15.3 % of them have moderate or severe disabilities. The allocation of home nursing care services is therefore an important issue. Service providers in Taiwan vary substantially across regions, and between rural and urban areas. There are no appropriate indices for describing the capacity of providers that it is due to the distances from care recipients. This study therefore aimed to describe and compare distance barriers for home nursing care providers using indices of the "profit willing distance" and the "tolerance limited distance". Methods This cross-sectional study was conducted during 2012 and 2013 using geocoding and a geographic information system to identify the distance from the providers' locations to participants' homes in urban (Taipei City) and rural (Hualien County) areas in Taiwan. Data were collected in-person by professionals in Taiwanese hospitals using the World Health Organization Disability Assessment Schedule 2.0. The indices were calculated using regression curves, and the first inflection points were determined as the points on the curves where the first and second derivatives equaled 0. Results There were 5627 participants from urban areas and 956 from rural areas. In urban areas, the profit willing distance was 550–600 m, and we were unable to identify them in rural areas. This demonstrates that providers may need to supply services even when there is little profit. The tolerance limited distance were 1600–1650 m in urban areas and 1950–2000 m in rural areas. In rural areas, 33.3 % of those living inside the tolerance limited distance and there was no provider within this distance, but this figure fell to just 13.9 % in urban areas. There were strong disparities between urban and rural areas in home nursing care resource allocation. Conclusions Our new "profit willing distance" and the "tolerance limited distance" are considered to be clearer and more equitable than other evaluation indices. They have practical application in considering resource distribution issues around the world, and in particular the rural–urban disparities for public resource.